2012
DOI: 10.1021/ic2025236
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Metal-Binding Ligands with the Zinc Proteome: Zinc Sensors and N,N,N′,N′-Tetrakis(2-pyridylmethyl)ethylenediamine

Abstract: The commonly used Zn2+ sensors, TSQ and Zinquin, have been shown to image Zn-proteins as a result of the formation for sensor-Zn-protein ternary adducts not Zn(TSQ)2 or Zn(Zinquin)2 complexes. The powerful, cell permeant chelating agent TPEN is also used in conjunction with these and other Zn2+ sensors to validate that the observed fluorescence enhancement seen with the sensors depends on intracellular interaction with Zn2+. We demonstrated that the kinetics of reaction of TPEN with cells pretreated with TSQ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…43-45 As shown elsewhere, reacting TSQ-Zn-protein adducts with TPEN results in a decrease in fluorescence through either ligand substitution or competitive adduct formation with TSQ-Zn-proteins. 29 Thus, the resulting depletion of TSQ-fluorescence after treatment with TPEN provides validity to the claim that Zn-proteins broadly maintained their metal cofactors after electrophoresis using NSDS-PAGE. Overall, these data support the conclusion that NSDS-PAGE offers a viable method for detecting protein-bound metals after electrophoresis.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…43-45 As shown elsewhere, reacting TSQ-Zn-protein adducts with TPEN results in a decrease in fluorescence through either ligand substitution or competitive adduct formation with TSQ-Zn-proteins. 29 Thus, the resulting depletion of TSQ-fluorescence after treatment with TPEN provides validity to the claim that Zn-proteins broadly maintained their metal cofactors after electrophoresis using NSDS-PAGE. Overall, these data support the conclusion that NSDS-PAGE offers a viable method for detecting protein-bound metals after electrophoresis.…”
Section: Resultsmentioning
confidence: 67%
“…Of this total, EDTA, alone, accounts for a significant fraction, about one-third, according to previous studies. 28, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Since TPEN forms ternary adducts with Zn-proteins, the results also suggested that NPG A had not formed NPG-Zn-protein species that could be converted to TPEN-Zn-proteins. 25 …”
Section: Resultsmentioning
confidence: 99%
“…Zinquin fluorescence was punctate consistent with sequestration into endosomes, lysososmes, or other organelles [29] while FluoZin fluorescence was diffuse consistent with predominantly cytoplasmic distribution. While the origin of Zn 2+ -dependent fluorescence by Zinquin and FluoZin remains under investigation and apparently involves interaction of the fluorphores with Zn 2+ -binding proteins rather than with an aqueous free-Zn 2+ pool in cells [30], the results are consistent with ZnPy cytotoxicity being mediated through increased intra-cellular Zn 2+ levels.…”
Section: Resultsmentioning
confidence: 82%